Analisis Pemilihan Kosakata dalam Buku Ajar Perspektif Rusydi Ahmad Thu’aimah - Nur Aini Puji Mastutik; Mirwan Ahmad Taufiq (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2021)
Textbooks and vocabulary (mufradāt) are equally important in learning Arabic. Because without choosing the correct wording (mufradāt) in Arabic texts, it will result in the inability of students to understand the lesson well. This study aims to reveal the vocabulary used by Arabic books and the suitability of the wording with the theory initiated by Ahmad Rusydi Thu’aimah. The method used in this study is a qualitative method using content analysis as a technique in research. For data processing and presentation, researchers focus on the theory of Rusydi Ahmad Thu’aimah as a guide for the data acquisition process. While the research results were found 127 (mufradāt) in the book, there were some congruences and discrepancies between Rusydi Ahmad Thu’aimah theory and Arabic textbooks. Among the appropriate bases between books and approaches are: the basis of frequency. the cause of range. the cause of significance. the cause of Arabic. While the other basis, namely the basis of availability, familiarity, and coverage, there is no match between theory and Arabic textbooks.